Economic Development as a Method of Foreign Policy Risk Compensation: The Case of Armenia - N. A. Dunamalyan; V. S. Davtyan; A. A. Tavadyan (Международная аналитика, 2023)
Throughout a 35-year period, the Armenian economy has withstood numerous crises and political shocks, including the Spitak earthquake, the fi rst Karabakh war, a decline in GDP by over 50 %, transport blockades, and the 2008 economic crisis. The aftermath of the 2020 44-day war in Nagorno-Karabakh introduced new risks and drastically altered the country’s development and economic conditions. Despite the broader context of international confrontation, which has spilled over into military conflict in Ukraine, the Armenian economy has created possibilities for growth under geopolitical uncertainty. In the short-term perspective, these developments have had a positive impact on economic growth in 2022. However, the continuity of such impact on the Armenian economy depends on the government’s concrete approaches and further existence of current conditions. The article aims to explore the interrelationship between Armenia’s foreign policy and economy in the context of global and regional changes. The policy of the Armenian government is considered through the prism of the main features of the notion “small state,” with particular attention paid to the logic of changes in foreign policy throughout the entire period of independence. By utilizing large-scale statistical data, the article presents the causes of the radical growth of Armenia’s GDP in 2022 while simultaneously analyzing its structure. The development of the country’s energetic system is presented as an illustration of the establishment of a separate field that combines export possibilities, investment potential, and risk formation. The article also covers the reasons for the relative stability of the Armenian economy under the background threat of military escalation.